Tourist and Recreational Opportunities of Vinnytsia Region in the Context of Ukrainian Modern Tourism Development - SAMBORSKA, Oksana (Journal of Environmental Management and Tourism, 2021)
Today tourism is considered one of the promising areas of socio-economic development of the country, regions and cities. After all, the tourism industry generates 11% of the world's gross domestic product, and the tourism industry - 4.2%. Analysis of the situation in Ukraine shows that the tourism industry is gradually developing, although not characterized by stable growth. So, if in 1997 our country was visited by 337 000 foreign tourists, in 2003 - 591 000, and in 2004 - 436 000 foreign tourists. A similar fluctuation over the years in the number of tourists is typical for domestic tourism. At the same time, in our country there are all the prerequisites for the development of tourism: historical, geographical, natural, economic, socio-demographic. Accordingly, the causes of instability are a number of problems that slow down the development of tourism in Ukraine and hinder the development of the tourism industry. The modern development of Ukraine and its regions is ensured through the creation of effective management of industries at all levels of government with the delineation of local powers in this area. The development of the tourism sector, outlining priorities and ways to address this issue also opens up great opportunities for the country. The transformation of Ukraine into a world-renowned tourist state requires coordination and control over the activities of sectors of the economy on which the quality of tourist services, transport services, trade, creation of souvenirs, publishing, and advertising propaganda depends.